Pan, tierra y tapaboca: Luis Muñoz Marín y el breve interregno democrático del Partido Popular (Puerto Rico, 1938-1948) - JOSÉ F. BUSCAGLIA (Diálogos Latinoamericanos, 2013)
The launching in 1938 and the implementation over the next two decades of the reform program of the Popular Democratic Party (PPD) resulted in a radical transformation of the economy and a massive realignment of social forces in Puerto Rico. That process was officially known as the ‘Puerto Rican Miracle’ and, at the height of the Cold War, it was promoted by the USA as a ‘peaceful revolution’ in contraposition to the armed insurrection commanded by Fidel Castro in Cuba. This article describes a process less transparent and democratic that, conforming to Latin American populist traditions, unfolded within a continuum where internal debate inside the PPD and opposition forces in the public sphere, were systematically supressed as Luis Muñoz Marin rose to become the uncontested leader of the movement. The experiment was also a failed exercise in decolonization that brought dire consequences to large sectors of Puerto Rican society.